The Remnants of Ancient Java as a Sign System in Bagelen Central Java - Niken Wirasanti (IHiS (Indonesian Historical Studies), 2022)
This research explored the cultural traces of the Ancient Mataram community in South Kedu, Bagelen region, Central Java. There areabundant archaeological data to study these traces – Hindu and Buddhist statues, lingga-yoni, lingga pathok, rings, lamps, and fiveinscriptions, namely the Watukura (902 AD, Kayu Ara Hiwang (911 AD), Sipater (circa 900 AD), Ayam Têas (901 AD), and Pendem (881 AD). In addition, there are more than 26 archaeological sites in Bagelen region. Statues, lingga-yoni, lamps, and rings are correlated with the contents of the inscriptions, all of which show how the system and social structure of the residents worked and functioned in Bagelen region. These artifacts are a system of sign that describes the religious activities during the Rakai Watukura Dyah Balitung period of the Ancient Mataram. The research was aimed to obtain an overview of how material culture as a sign system is interpreted by the community. The research method used was a structural approach by analyzing signs and meanings of artifact data and inscriptions. The findings showed how the manifested culture in Bagelan region reflected a certain spirituality concept with local and cultural identification.